2004
DOI: 10.1063/1.1631919
|View full text |Cite
|
Sign up to set email alerts
|

Water in nanopores. I. Coexistence curves from Gibbs ensemble Monte Carlo simulations

Abstract: Coexistence curves of water in cylindrical and slitlike nanopores of different size and water-substrate interaction strength were simulated in the Gibbs ensemble. The two-phase coexistence regions cover a wide range of pore filling level and temperature, including ambient temperature. Five different kinds of two-phase coexistence are observed. A single liquid-vapor coexistence is observed in hydrophobic and moderately hydrophilic pores. Surface transitions split from the main liquid-vapor coexistence region, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
146
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(158 citation statements)
references
References 112 publications
10
146
0
2
Order By: Relevance
“…This phase diagram is based on the four following results: (i) water adsorption in Al(OH)(1,4-ndc) happens at pressure lower than P sat ; (ii) the adsorption transition is continuous, meaning the confined water is supercritical at 298 K; (iii) adding methyl groups increases the adsorption pressure; (iv) as confinement increases, the critical point shifts to lower temperature. 45 The diagram obtained, represented in Fig. 9, is markedly different from that inferred for hydrophobic zeolites, where adsorption happens at P > P sat .…”
Section: Nature Of the Adsorption Transition; Phase Diagram Of The Comentioning
confidence: 68%
“…This phase diagram is based on the four following results: (i) water adsorption in Al(OH)(1,4-ndc) happens at pressure lower than P sat ; (ii) the adsorption transition is continuous, meaning the confined water is supercritical at 298 K; (iii) adding methyl groups increases the adsorption pressure; (iv) as confinement increases, the critical point shifts to lower temperature. 45 The diagram obtained, represented in Fig. 9, is markedly different from that inferred for hydrophobic zeolites, where adsorption happens at P > P sat .…”
Section: Nature Of the Adsorption Transition; Phase Diagram Of The Comentioning
confidence: 68%
“…Recent simulations of water in hydrophobic pores also illustrated the effect of curved surfaces on the values of local critical exponents [193]. In that study Brovchenko et al observed a sharp crossover for cylindrical surfaces, yielding an asymptotic value for the local order parameter larger than the value β 1 ≈ 0.82 measured for slitlike pores.…”
Section: Ordinary Transitionmentioning
confidence: 93%
“…The critical behaviour characteristic of the ordinary transition is expected to be observed in this case not too close to T c as one is dealing with the liquid-vapour transition near a weakly attractive surface, see the discussion in Section 2.6. Of course, the geometry is slightly different to the wedge-shaped geometries discussed so far in the literature, but nevertheless the kind of systems discussed in [193] seems to be a good candidate to study the effect of (generalised) edges on the local critical behaviour experimentally in the future.…”
Section: Ordinary Transitionmentioning
confidence: 99%
“…For example, capillary critical temperatures in confined geometries are reported experimentally for SF 6 in porous glass and several gases in MCM-41 by Thommes et al 13 and Morishige Findenegg, 14 respectively; the shift in the critical temperature is found to have linear dependence on the inverse pore width. Numerous theoretical studies and molecular simulations including density function theory [15][16][17][18] and Monte Carlo ͑MC͒ simulations [19][20][21][22][23][24][25] were performed to understand capillary condensation. Vishnyakov et al 26 were the first to perform MC simulations systematically on carbon slit pores and studied the shift of the vapor-liquid critical point under confinement.…”
Section: Introductionmentioning
confidence: 99%